Shear Reinforcement of Existing Reinforced Concrete Beam Using Deep Embedment Method - Ilham Akbar; Ridwan; Muhammad Ikhsan (Rekayasa Sipil, 2024)
The load capacity of old reinforced concrete structures must be increased to meet current standards. This might be due to increased load needs, inadequate shear provisions in the original design, material degradation, or rising demands for shear capacity related to flexural strengthening. This research demonstrates a method that effectively repairs RC beams using embedded steel bars. Loading history was reproduced in the form of cracking within the elastic range in 2000 x 150 x 200 mm beam. The beam was repaired and then reloaded to failure in the experimental test. The results show that the contribution of steel bars embedded in the core of the RC beam to the load capacity can be significant. The highest initial stiffness of the strengthened beam was 13,07 kN/mm, which was 69% higher than the control beam, while the maximum load of the strengthened beam was 43 kN with the deflection at 13,00 mm, 43% higher than the control beam. The cracks developed during the reinforced beam’s second load phase were identical to the first, and the shear capacity increased more than the control beam.